Efficacy and safety of imiquimod in the treatment of subclinicaland clinical forms of persistent cervical papillomavirus infection in patients of early reproductive age - N I Tapilskaya; I N Vorobtsova; S N Gaidukov; S N Proshin (IP Berlin A.V., 2015)
Objectives. HPV infection is a major risk factor for cervix cancer. This study evaluated cervical application of imiquimodfortreatment of subclinical (flat condyloma) and clinical (CIN I, LSIL) manifestations of human papillomavirus infection. Methods. An open controlled study (n=28) efficacy and safety of imiquimod (5% cream Aldara) in 1-2 months. Results. All patients treated had complete clinical responses. Clinical efficacy of treatment at 1 month was 96,4%, in 2 months - 100%. Microbiological efficacy (full HPV-clearance) achieved in 60,7% of cases, in other cases there was a decrease in viral load. Elimination of the 16 types of virus was achieved in 80% of cases. Immunocytochemical study showed higher levels of expression of Toll-like receptor 4 and 9 type in the endo - and ectocervix after treatment. Undesirable effects were not grounds for termination of treatment.Conclusions. The trial does support the feasibility and acceptability of the use of imiquimod on the cervix in treatment of manifestations of human papillomavirus infection.